Simulation the distribution of thermodynamic temperatures and microwave radiation of the human head. (July 2020) - Kublanov, Vladimir S.; Borisov, Vasilii I.; Babich, Mikhail V.
Highlights: Model of the brain microwave radiation in the form of a three-dimensional distribution of the microwave brightness temperature are proposed. Geometry of a real MRI image of a human head was used for modeling. Verification data made by IR thermograph practically coincide with the results of numerical modeling. The methodology proposed in the article allows simulation of a human body voxel models using only free and open source software. Abstract: Background and Objective: The influence of biophysical parameters on the formation of microwave radiation of the human head is poorly studied. Existing approaches to modeling microwave radiation of the human head have limitations associated with simplifying the geometry of human anatomy. The article proposes methodological solutions for numerical modeling of microwave radiation of the brain biological tissues using the geometry obtained from MRI data. Methods: The geometrical characteristics of biological tissues in model are determined using an MRI image of the head. The methodology proposed in the article allows simulation of a human body voxel models performed the Pennes bio-heat transfer equation using the Fenix software package. Results: Modeling evaluations have shown that anatomical tissues heterogeneities on the surface of the head form temperature gradient of up to 2.0 K, and changes of the microwave radiation up to 0.3 K. Conclusions: Verification data made by IR thermograph practically coincide with the results of numerical modeling. The fluctuations of the brain microwave radiation are not only the result of thermal processes in its tissues, but are determined by the dynamics of its thermoregulation processes and are an indicator of changes in the physiological processes occurring in it.